Practical accounting 1 - Valix, Conrado T. (Manila, Philippines : GIC Enterprises & Co. Inc., 2008)
This book is primarily intended as a Reviewer in Practical Accounting Problems I in the Philippine CPA Licensure Examinations.
1. Statement of Financial position -- 2. Income statement and comprehensive income -- 3. Discontinued operations -- 4. Accounting changes -- 5. Segment Reporting -- 6. Interim reporting -- 7. Cash and cash equivalents -- 8. Bank reconciliation -- 9. account receivable -- 10. Receivable Financing -- 11. Notes receivable and loan impairment -- 12. Inventory -- 13, Inventory valuation -- 14. Gross profit and retail method -- 15. Investments -- 16. Investment in equity securities -- 17. Investment in associate -- 18. Held to maturity securities -- 19. Fund and other investments -- 20. Derivatives -- 21. Property , plant and equipment -- 22. Land, building and machinery -- 23. Borrowing cost -- 24. Depreciation -- 25. Depletion -- 26. Revaluation -- 27. Impairment of asset -- 28. Intangible assets -- 29. Research and development cost -- 30. Current Liabilities -- 31. Provision and contingent liability -- 32. Note payable and debt restructure -- 33. Bonds payable -- 34. Operating lease and leaseback -- 35. Finance lease-Lessee -- 36. Finance Lease - Lessor -- 37. Employee benefits -- 38. Accounting for income tax -- 39. Shareholders equity -- 40. Share-based compensation -- 41. Retained earnings -- 42. Book value and preference dividends -- 43. Earnings per share -- 44. Single entry -- 45. Cash and accrual basis -- 46. Error Correction -- 47. Cash flow - Operating -- 48. Cash Flow- Investing and financing -- cash flow - comprehensive -- 50. Hyperinflation.
Keywords: ACCOUNTING